2014
DOI: 10.3109/08990220.2014.911172
|View full text |Cite
|
Sign up to set email alerts
|

Pudendal and median nerve sensory perception threshold: A comparison between normative studies

Abstract: Comparing normative data of multiple studies shows a variety of results and poor agreement. Therefore, referring to normative data of other studies should be handled with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…We did not find gender differences at the testing site for the index finger, which is accordant with reports from Quaghebeur et al (Quaghebeur and Wyndaele, 2014 ) and Galvão Mde et al ( 2005 ). However, Takekuma et al revealed gender effects on CPT values for the index finger under stimuli of 250 and 5 Hz in a community-dwelling of 1,000 Japanese, of which males had higher CPT values (Takekuma et al, 2000 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We did not find gender differences at the testing site for the index finger, which is accordant with reports from Quaghebeur et al (Quaghebeur and Wyndaele, 2014 ) and Galvão Mde et al ( 2005 ). However, Takekuma et al revealed gender effects on CPT values for the index finger under stimuli of 250 and 5 Hz in a community-dwelling of 1,000 Japanese, of which males had higher CPT values (Takekuma et al, 2000 ).…”
Section: Discussionsupporting
confidence: 93%
“…The CPT device has been applied in the diagnosis and evaluation of many clinical conditions, of which diabetic neuropathy is the most common (Rendell et al, 1989 ; Katims et al, 1991 ; Rendell and Bamisedun, 1992 ; Lee et al, 1997 ; Ro et al, 1999 ; Menkes et al, 2000 ; Kurozawa and Nasu, 2001 ; Oishi et al, 2002 ; Takekuma et al, 2002 ; Cui et al, 2003 ; Prendergast et al, 2004 ; Lander et al, 2007 ; Putz et al, 2009 ; Nather et al, 2011 ; Griffith et al, 2014 ). However, more than one study has found differences between the reference values of the research subjects and those provided by the manufacturer (Galvão Mde et al, 2005 ; Quaghebeur and Wyndaele, 2014 ), and the influence of factors such as age and gender on CPT values has not been illustrated consistently among various studies (Evans et al, 1992 ; Takekuma et al, 2000 ; Tseng et al, 2002 ; Seong et al, 2009 ). Therefore, the objective of our study was to explore CPT distribution properties of Chinese subjects and to investigate different influencing factors of CPT.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison between Neuval database II data and normative data of other studies showed a weak agreement for pudendal nerve CPTs. The median nerve CPTs showed a better agreement [23] .…”
Section: Sensory Functionmentioning
confidence: 88%
“…The pudendal and median nerves showed deviating CPT values in healthy volunteers. The pudendal nerve measurements showed deviating values for 2 KHz in almost 50% [23] . Normative data in our study showed mostly no agreement with the data from other studies in healthy volunteers or control groups [23] .…”
Section: The Sensory Function Of the Pudendal And Median Nerves In Healthy Volunteersmentioning
confidence: 95%
“…A previous study using Neurometer 1 device with large surface electrode measured at the left index finger also reported that women showed lower CPT values than men at 250 Hz and 5 Hz frequency stimulus which are correlated to small fiber function [1,18]. However, another study showed that no statistical gender differences were shown for the median nerve [28]. Other studies using thermal perception threshold also showed that men had a higher perception threshold compared to women [29,30].…”
Section: Plos Onementioning
confidence: 92%